Analysis of GHG Reduction in Non-ETS Energy Sector. (August 2015) - Lauka, Dace; Blumberga, Andra; Blumberga, Dagnija; Timma, Lelde
Abstract: Member states of the European Union have undertaken to reduce GHG emissions and to achieve targets in 2020 and 2030. By using the system dynamic model, it is possible to analyze the possible GHG emission reduction, and the impact of suggested policy instruments on this reduction.